2017
DOI: 10.1002/lno.10522
|View full text |Cite
|
Sign up to set email alerts
|

Wind and buoyancy driven horizontal exchange in shallow embayments of a tropical reservoir: Lake Argyle, Western Australia

Abstract: Many factors including depth, vegetation density, wind, and gyres may act to influence the littoral exchange in a water body but very few studies have investigated the interaction between more than two of these factors at any time. To investigate these controls on horizontal exchange in a large tropical reservoir, we conducted a 9‐d intensive field experiment in Lake Argyle, Western Australia. The experiment began with a 7‐d cooling period that generated water in the shallows of the reservoir embayments that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 65 publications
(93 reference statements)
0
22
0
Order By: Relevance
“…The velocity profile has large gradients near the water surface and the lake bed, but is constant at the mid-layer, which is totally different from the two-layer velocity profile under the baroclinic scenario. In other words, a smooth and log layer velocity profile under the barotropic scenario is replaced by the two-layer daytime stratification and reduce the mixed layer depth by increased solar radiation attenuation and reduced wind mixing [32,33,72]. In this paper, it is found that the three-dimensional temperature structures in a small and shallow lake can be affected by velocity retardation and vertical mixing reduction due to littoral macrophytes, which have not yet been reported in the literature before.…”
Section: Effects Of Weak Stratificationmentioning
confidence: 63%
See 3 more Smart Citations
“…The velocity profile has large gradients near the water surface and the lake bed, but is constant at the mid-layer, which is totally different from the two-layer velocity profile under the baroclinic scenario. In other words, a smooth and log layer velocity profile under the barotropic scenario is replaced by the two-layer daytime stratification and reduce the mixed layer depth by increased solar radiation attenuation and reduced wind mixing [32,33,72]. In this paper, it is found that the three-dimensional temperature structures in a small and shallow lake can be affected by velocity retardation and vertical mixing reduction due to littoral macrophytes, which have not yet been reported in the literature before.…”
Section: Effects Of Weak Stratificationmentioning
confidence: 63%
“…daytime stratification and reduce the mixed layer depth by increased solar radiation attenuation and reduced wind mixing [32,33,72]. In this paper, it is found that the three-dimensional temperature structures in a small and shallow lake can be affected by velocity retardation and vertical mixing reduction due to littoral macrophytes, which have not yet been reported in the literature before.…”
Section: Effects Of Macrophytesmentioning
confidence: 73%
See 2 more Smart Citations
“…In aquatic environments, convective exchange flows play an important role in the transport of nutrients, pollutants and chemical substances between the littoral and pelagic regions of lakes or reservoirs under weak wind conditions and in the absence of other sources of momentum (e.g., river flows) [1][2][3]. The convective exchange flows are mainly driven by a density difference in the horizontal direction, which can be caused by nearshore topographic changes [4], vegetation shading [5], or turbid patches in the water [6].…”
Section: Introductionmentioning
confidence: 99%